2020
DOI: 10.1016/j.acalib.2020.102253
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of overnight learning commons: A comparative study

Abstract: This study explores the overnight usage of Chi Wah Learning Commons and The University of Hong Kong Libraries on the same campus. By adopting quantitative research, it investigates students' preferences in these areas and levels of social capital in the library, further, it explores the similarities and differences of user behavior between the university's undergraduate and postgraduate students. Our findings showed that HKUL had not taken full advantage of its prime location and comprehensive collection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Learning commons become more favorable spaces for various learning and non-learning activities for participants from different faculties, especially many learning commons in this university open 24 h (Chan et al , 2020). With ubiquitous access to library resources and increasing electronic resources (Wang et al , 2016), universities should create multiple types of learning spaces (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Learning commons become more favorable spaces for various learning and non-learning activities for participants from different faculties, especially many learning commons in this university open 24 h (Chan et al , 2020). With ubiquitous access to library resources and increasing electronic resources (Wang et al , 2016), universities should create multiple types of learning spaces (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Libraries are transforming from a space to store books into integrated cultural, meeting and learning spaces that tend to operate 24/7 (Yip et al , 2019; Chan et al , 2020a; Kim et al , 2020; Leung et al , 2022; Ho et al , 2022a,b; Jiang et al , 2022; Wong and Chiu, 2023). Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Mobile devices should be only used for preparing and uploading homework photos and placed outside the learning space after use. From the perspective of school management, mobile devices should be prohibited in the learning space, different from university settings (Leung et al ., 2022; Zhou et al ., 2022; Chan et al ., 2020; Deng et al ., 2019; Yip et al ., 2019).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%